Clinical Significance of Extraluminal Compressions according to the Site of the Esophagus - Sung Ik Pyeon; Gwang Ha Kim; Jung Bin Yoon; Hye Kyung Jeon; Bong Eun Lee (Yong Chan Lee, 2017)
Background/Aims: Differentiation of an extraluminal compression from a true subepithelial tumor (SET) in the esophagus by using endoscopy alone is often difficult. EUS is known as the best method for differentiating an extraluminal compression from a true SET. Extraluminal compression in the esophagus is occasionally observed, but its clinical significance has been rarely reported. Therefore, we aimed to evaluate the clinical significance of extraluminal compression in the esophagus according to the location of the lesion. Materials and Methods: Sixty-one patients were diagnosed as having an extraluminal compression in the esophagus by using EUS between January 2006 and March 2014. Some patients underwent chest computed tomography for accurate diagnosis. Results: The extraluminal compression was located at the mid-esophagus in 26 cases, lower esophagus in 22 cases, and upper esophagus in 13 cases. Of the 61 cases, 55 were caused by normal structures and 6 were caused by pathological lesions. The causes of the normal structures were the aorta, vertebra, trachea, left main bronchus, azygos vein, and diaphragm. The causes of the pathological lesions were engorged vessels and calcified lymph nodes. The posterior wall was the most frequent location of the extraluminal compression. However, the lesions in the anterior and right walls showed a higher frequency of pathological lesions than those in other sites. Conclusions: If the extraluminal compression is found in the anterior and right walls of the esophagus, more careful evaluation should be performed considering the high frequency of pathological lesions in the site.